Dampak Program Gizi Berbasis Sekolah terhadap Status Gizi, Anemia, dan Pengetahuan Gizi pada Anak Sekolah Dasar di Kabupaten Pidie, Aceh, Indonesia: The impact of School-Based Nutrition Program on Nutritional Status, Anemia, and Nutrition Knowledge Among Elementary School Children in Pidie District, Aceh, Indonesia - Ahmad, Aripin; Arifin, Syuja' Rafiqi; Fitrianingsih, Eva; Arnisam, Arnisam (Amerta Nutrition, 2026)
Background: School-age children in Aceh are vulnerable to malnutrition, with 24.1% experiencing stunting and 12.3% exhibiting wasting, primarily due to unbalanced diets, skipping breakfast, and unhealthy snacking habits. Objectives: This study evaluates the impact of a School-Based Nutrition Program on nutritional status, anaemia, nutrition knowledge, and Clean and Healthy Behaviour (CHB) among elementary students in Pidie District, Aceh. Methods: A quasi-experimental pre–post study was conducted among 290 elementary students as part of the School-Based Nutrition Program, which included thrice-weekly meal provision, nutrition education, and CHB promotion. Nutritional status (BMI-for-age, height-for-age), anemia (hemoglobin levels), nutrition knowledge, and CHB practices (interviews) were assessed. Data were analyzed using chi-square and t-tests at a 95% confidence level. Results: Anemia prevalence decreased by 4.4%, stunting by 2.0%, and overweight by 4.9%. The height-for-age z-score slightly improved from -1.84±0.93 to -1.78±0.91. Students also showed better nutrition knowledge and CHB practices. While the program had no significant impact on reducing anemia, stunting, and BMI-for-age (p-value=0.120; p-value=0.887; p-value=0.148), it significantly improved nutrition knowledge and CHB behavior (p-value=0.015; and p-value=0.012). Conclusions: The School Based Nutrition Program effectively improved nutrition knowledge and Clean and Healthy Living Behaviour (CHLB). However, the short-term implementation did not yet lead to measurable improvements in nutritional and anemia status. To enhance future program outcomes, structured monitoring is crucial to ensure food adequacy, food safety, and the effective integration of nutrition education.